The potential of aloe vera gel utilization for skin wound healing in rats based on GC–MS and HPLC chemical profile - Nadia Mohamed Said Arafa; Huda Mohammad Ahmad Hummadi; Gehan Moustafa Badr (Journal of Basic and Applied Zoology)
Abstract Background Wound healing is a restoration process of tissue integrity and function targeting reducing the healing time and complications with priority of available, acceptable and affordable medication. The study aimed to evaluate wound healing of aloe vera gel as raw or ethanol extract on a dorsal full thickness circular wound in Wistar rats. Rats subjected to the excision surgery were grouped into: control (+ ve), without treatment. and Kenacomb, aloe raw gel and aloe ethanol extract applied groups for 3, 7, 14 and 21 days for treatment evaluation. The study chromatographically quantified anthraquinones and identified the raw gel and extract’ compounds. The evaluation was through the assessment of the wound contraction and complete blood count, serum interleukin-4 and skin tissue proline, hydroxyproline, glycine, malondialdehyde, nitric oxide contents and skin histopathology investigation at tested intervals. Results Raw gel and extract contained in μg/ml, aloin A (9.23 and 17.22), aloin B (8.87 and 10.31) and emodin (11.66 and 12.66), respectively. The predominates identified percentage in raw gel were coumarins (34.93), fatty acids (28.45), phytosterols (7.77) and tocopherols (8.44) and in gel extract were phytosterols (49.39), fatty acids (29.16) and tocopherols (3.70). Results after 21 days were recorded in + ve control 80.50% wound contraction and showed significantly decreased values of IL-4, lymphocytes, Hb, RBCs and skin glycine, proline, hydroxyproline and NO. Neutrophils, monocytes, platelets and MDA were significantly increased. Histologically revealed epidermal acanthosis, inflammatory infiltration, fibrosis with hair follicles and sebaceous glands loss and dermal hemorrhage. Aloe raw gel revealed incomplete healing (91.79%) and failed to normalize IL-4, lymphocytes, neutrophils and the skin glycine and NO contents. Skin showed moderate epidermal acanthosis, and dermis had fibrosis, hemorrhage and loss of sebaceous glands and hair follicles. The extract group acquired 100% healing, normalized tested parameters and showed skin tissue thinning epidermis and intact dermal tissue with sebaceous glands and hair follicles. Conclusion Results revealed aloe gel ethanol extract advantage over raw gel for wound healing which may be related to chemical constituents’ variation interpreted in interest to the extract as an efficient therapeutic, cost-effective, available wound healing material.